The strategy of PT. Kereta Api Logistik Maintaining Brand Image - Nanda Anggun Pratiwi; Susi Yunarti (Jurnal Manajemen Bisnis, 2025)
This research examines the branding strategy of PT Kereta Api Logistik (KALOG), a state-owned logistics company in Indonesia, focusing on how operational innovations and the "Ispossible" rebranding initiative have shaped its brand image. The study utilizes a qualitative case study approach, with data collected from interviews and company records. Findings indicate that KALOG's integration of traditional and digital media, along with its focus on customer engagement through digital activations and CSR activities, has strengthened its brand presence. The study highlights the importance of aligning corporate actions with brand values, providing insights for both state-owned and private logistics companies.